Effect of sleep deprivation on the electrophysiological signature of habituation to noxious laser stimuli - Schuh-Hofer, Sigrid; Baumgärtner, Ulf; Treede, Rolf-Detlef (European journal of pain, 2015)
Background: Sleep deprivation induces hyperalgesia. However, this pronociceptive effect is not reflected at the electrophysiological level, since sleep restricted subjects show amplitude reduction of Laser-evoked Potentials (LEP). We aimed to explore the contribution of habituation to this paradoxical LEP amplitude decline. Methods: We compared LEP's of 12 healthy students (23.2 ± 1.1 years) after habitual sleep (HS) and a night of total sleep deprivation (TSD). Twelve repetitive laser stimulus blocks (each comprising twenty stimuli) were applied under three attention conditions (‘focusing’ - ‘neutral’ - ‘distraction’ condition). Stimulus blocks were split in part 1 (stimulus 1-10) and part 2 (stimulus 11-20). The contribution of habituation to the TSD-induced LEP amplitude decline was studied by calculating the percentage amplitude reduction of part 2 as compared to part 1. Individual sleepiness levels were correlated with (1) averaged LEP's and (2) the degree of habituation. Results: TSD induced hyperalgesia to laser stimuli (p < 0.001). In contrast, depending on the attention condition, the P2 amplitude of the N2P2-complex was significantly reduced (‘focusing’: p = 0.004; ‘neutral’: p = 0.017; distraction: p = 0.71). Habituation of the P2 amplitude to radiant heat was increased after TSD (‘focusing’: p = 0.04; ‘neutral’: p < 0.001; distraction: p = 0.88). TSD had no significant effect on N1 amplitudes (p > 0.05). Individual sleepiness correlated negatively with averaged P2 amplitudes (p = 0.02), but not with the degree of habituation (p = 0.14). Conclusion: TSD induces hyperalgesia and results in attention-dependent enhanced habituation of the P2 component. Increased habituation may - to a substantial degree - explain the TSD-induced LEP-amplitude decline.